MODELING OF BONUS-MALUS SYSTEM WITH FREQUENCY AND SEVERITY COMPONENTS. - O. Klesov (Kherson State University, 2010)
Bonus-Malus systems are widely used all over Europe and Asia. Each client of insurance company is determined to same class. According to this, insurance premium is defined. Depending on the claim frequency and claim severity, client could move from one insurance class to another, receiving discount on insurance premium (bonus class) or a fine (malus class). The aim of this work is estimation of parameters of claim frequency and severity distributions in which the company receives the highest profit. Using C++ features was carried out modeling and estimation of values of frequency and severity component of bonus-malus system in which company receives the highest financial return. Was also written special random number generator, which can be used in further researches.